Impact of skin-to-skin contact at birth on exclusive breastfeeding and the regulation of vital signs - Brenda Rosario Rosas-Herrera; Julieta Rodríguez de Ita; Jorge A Martínez-Cardona (Instituto Nacional de Salud Pública, 2019)
[Not available]